PENERAPAN E-MODUL ECOPRINT FLIPBOOK BERBASIS PROJECT BASED LEARNING UNTUK MENINGKATKAN MOTIVASI DAN KREATIVITAS SISWA - Luftia Firdausia; Ana Fitrotun Nisa; Heri Maria Zulfiati; Insanul Qisti Bariyah (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2024)
This research aims to describe the application of the Ecoprint Flipbook E-Module based on the Tri-N (Niteni, Nirokke, Nambahi) integrated Project Based Learning (PjBL) learning model in science and science learning in 4th students elementary school. This research is descriptive qualitative in nature. The research subjects involved 27 students, consisting of 14 male students and 13 female students. Data was collected through interviews, observation, questionnaires and documentation. Data analysis techniques include data reduction, data presentation, and drawing conclusions. The importance of the Ecoprint Flipbook E-Module helps students increase student motivation and creativity in learning science and science. The results of interviews with teachers show that students are motivated by implementing the Ecoprint Flipbook E-Module. Data analysis shows an increase in student motivation and creativity. The Ecoprint Flipbook e-Module has proven effective in increasing student motivation and creativity in elementary schools. The application of the Ecoprint Flipbook E-Module in science and science learning for 4th students elementary school students has had a positive impact because it is able to increase motivation and creativity in learning so that researchers recommend teachers and other researchers to use or adopt and perfect this module. Keyword: ecoprint, flipbook, science